Light on the Landscape - Neill, William (Rocky Nook, 2020)
See the images and read the stories behind the creative process of one of America's most respected landscape photographers, William Neill. For more than two decades, William Neill has been offering his thoughts and insights about photography and the beauty of nature in essays that cover the techniques, business, and spirit of his photographic life. Curated and collected here for the first time, these essays are both pragmatic and profound, offering readers an intimate look behind the scenes at Neill's creative process behind individual photographs as well as a discussion of the larger and more foundational topics that are key to his philosophy and approach to work. Drawing from the tradition of behind-the-scenes books like Ansel Adams' Examples: The Making of 40 Photographs and Galen Rowell's Mountain Light: In Search of the Dynamic Landscape, Light on the Landscape covers in detail the core photographic fundamentals such as light, composition, camera angle, and exposure choices, but it also deftly considers those subjects that are less frequently examined: portfolio development, marketing, printmaking, nature stewardship, inspiration, preparation, self-improvement, and more. The result is a profound and wide-ranging exploration of that magical convergence of light, land, and camera. Filled with beautiful and inspiring photographs, Light on the Landscape is also full of the kind of wisdom that only comes from a deeply thoughtful photographer who has spent a lifetime communicating with a camera. Incorporating the lessons within the book, you too can learn to achieve not only technically excellent and beautiful images, but photographs that truly rise above your best and reveal your deeply personal and creative perspective-your vision, your voice.
Online resource; Title from title page (viewed April 22, 2020)